Scottish Kiltmaking Design Process. (2nd September 2021) - Loranger, David; Sanders, Eulanda
Abstract: The kilt is one of the most recognizable garments in the world and is an important element in Scottish national culture, and although the Scottish kilt has existed for approximately 500 years, there is scant literature available that documents Scottish kiltmaking design and production processes. Due to this lack of attention it is important to understand kilts and kiltmakers more deeply. Therefore, the purpose of the present research was to understand common skills and production techniques used by Scottish kiltmakers. The present study utilized interviews with kiltmakers ( n = 17), observations and video recordings, and creation of a kilt prototype to document the kiltmaking process. Emergent themes included indigenous knowledge, skill set, planning, sewing processes and techniques key to the process of kiltmaking. The research successfully explored: (a) the learning process that kiltmakers undergo, (b) the unique aspects of the Scottish kiltmaking process that differentiate it from other forms of tailoring and apparel professions, and (c) the salient design and production process utilized by Scottish kiltmakers. Limitations and future research are outlined.